Assessment of the effectiveness of interaction between enterprise structural units - Yanshuang, MA (Харківський національний автомобільно-дорожній університет, 2024)
In the qualification work, the essence and types of organizational structures of enterprise management by the interaction of their subdivisions are defined; the methods of designing the organizational structure of the enterprise are analyzed; a mechanism for improving the organizational structure of enterprise management is developed, which is based on the basic principles and criteria of efficiency and includes modern methods, tools and levers for building the organizational structure of enterprise management. The results of the work are analyzed Preiz LLC over the past three years; an assessment of the effectiveness of the organizational structure of the management of Preiz LLC was carried out; the efficiency of interaction of structural subdivisions of the enterprise has been investigated; the modeling of the organizational structure of the management of Preiz LLC has been carried out and its economic efficiency has been determined. Prospects for further research are associated with the use of specific methods for improving the organizational structures of enterprise management to ensure its competitive advantages.
Keywords: organizational structure of the enterprise; structure of enterprise management; interaction of departments; assessment of the effectiveness of interaction of departments